ANALISIS KUALITAS WEBSITE JADWALIBADAH TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN METODE WEBQUAL 4.0 - Kevin Lorenzo; Hasniati; Hamdan Arfandy (STMIK KHARISMA Makassar, 2021)
This study aims to measure the quality of the JadwalIbadah website based on usability quality, information quality, and interaction quality on user satisfaction. The method used in this research is WebQual 4.0. Based on the WebQual 4.0 method, there are three variables, namely usability, information quality, and interaction quality on user satisfaction. The results showed that the variables usability (X1), information quality (X2), and interaction quality (X3) where each independent variable had 90% effect on user satisfaction (Y) on the JadwalIbadah website. While the rest is influenced by external variables other than the webqual 4.0 variable. Based on the results of the analysis conducted, there is a positive relationship between the services provided by the JadwalIbadah website to the three variables, namely usability (X1), information quality (X2), and interaction quality (X3) so that the results are positive on user satisfaction (Y). So that the three variables have a significant effect on the quality of the Schedule of Worship website on user satisfaction (Y).